Reduced graphene oxide promoted assembly of graphene@polyimide film as a flexible cathode for high-performance lithium-ion battery. Issue 15 (28th February 2020) - Chang, Bin; Ma, Jian; Jiang, Tiancai; Gao, Li; Li, Yuanting; Zhou, Mingan; Huang, Yanshan; Han, Sheng
Abstract : G@PI/RGO is prepared by a combination of solvothermal reaction and carbonization. With good mechanical flexibility and high conductivity, it shows excellent performance when directly used as the cathode for LIB. Abstract : Organic carbonyl polymers have been gradually used as the cathode in lithium-ion batteries (LIB). However, there are some limits in most organic polymers, such as low reversible capacity, poor rate performance, cycle instability, etc., due to low electrochemical conductivity. To mitigate the limits, we propose a strategy based on polyimide (PI)/graphene electroactive materials coated with reduced graphene oxide to prepare a flexible film (G@PI/RGO) by solvothermal and vacuum filtration processes. As a flexible cathode for LIB, it provides a reversible capacity of 198 mA h g −1 at 30 mA g −1 and excellent rate performance of 100 mA h g −1 at high current densities of 6000 mA g −1, and even a super long cycle performance (2500 cycles, 70% capacity retention). The excellent performance results in a special layer structure in which the electroactive PI was anchored and coated by the graphene. The present synthetic method can be further applied to construct other high-performance organic electrodes in energy storage.